The Influence of Transformational Leadership Style and Work Motivation on Employee Performance at Arei Outdoor Gear Store - Pratama, Rizki Agung; Hidayat, Agi Syarif; Juwita, Juwita (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
Purpose: This study aims to examine the influence of transformational leadership and work motivation on employee performance at Arei Outdoor Gear Store and to analyse their simultaneous contribution to performance improvement. The scope of the investigation focuses on employees’ perceptions of leadership behaviour, motivational factors, and work performance in a retail organisational setting. Design/methodology/approach: A quantitative explanatory research design was employed using a survey method. Data were collected through structured questionnaires distributed to 111 employees and analysed using multiple linear regression with classical assumption tests. Findings: The results show that transformational leadership and work motivation have a positive and significant effect on employee performance, both partially and simultaneously, with motivation showing a strong contribution to performance enhancement. Research limitations/implications: The study is limited to a single retail organisation and a cross-sectional dataset, which may restrict generalisation to other sectors and broader populations. Practical implications: The findings suggest that organisations should strengthen inspirational leadership practices and employee motivation systems to improve performance and service quality. Originality/value: This research provides empirical evidence on the combined role of transformational leadership and work motivation in enhancing employee performance within the Indonesian retail sector context. Paper type: Research paper